Graphdiyne and its Assembly Architectures: Synthesis, Functionalization, and Applications. Issue 42 (23rd May 2019) - Yu, Huidi; Xue, Yurui; Li, Yuliang
Abstract: Graphdiyne (GDY), a novel one‐atom‐thick carbon allotrope that features assembled layers of sp‐ and sp 2 ‐hybridized carbon atoms, has attracted great interest from both science and industry due to its unique and fascinating structural, physical, and chemical properties. GDY‐based materials with different morphologies, such as nanowires, nanotube arrays, nanosheets, and ordered stripe arrays, have been applied in various areas such as catalysis, solar cells, energy storage, and optoelectronic devices. After an introduction to the fundamental properties of GDY, recent advances in the fabrication of GDY‐based nanostructures and their applications, and corresponding mechanisms, are covered, and future critical perspectives are also discussed. Abstract : Recent progress on graphdiyne, with its fascinating structure and physical and chemical properties, is summarized. Research efforts toward controllable electronic structure, chemical modification, and applications of graphdiyne in different research fields and corresponding mechanisms are discussed, and critical research insights into the future development of graphdiyne materials are proposed and presented.